2017
DOI: 10.7150/jca.18932
|View full text |Cite
|
Sign up to set email alerts
|

Selective Gastric Cancer Patients with Peritoneal Seeding Benefit from Gastrectomy after Palliative Chemotherapy: A Propensity Score Matching Analysis

Abstract: Background: The present study aimed to explore whether gastric cancer patients with peritoneal seeding after receiving palliative chemotherapy could benefit from gastrectomy and to identify patients with peritoneal seeding who should be selected to receive gastrectomy.Methods: A total of 201 gastric cancer patients were diagnosed with peritoneal seeding and received palliative chemotherapy. Propensity score matching (PSM) was performed to balance the selection bias.Results: After PSM, compared with non-gastrec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
5
11
1
Order By: Relevance
“…In this study, we have implemented a propensity score modeling, producing a matched cohort based on baseline characteristics, as well as the extent of initial biological disease, before palliative chemotherapy and response to chemotherapy. Our findings were consistent with previous studies that advocated conversion surgery if R0 resection could be achieved, even after adjusting for potential confounding factors [9,10,12,21,22]. It is noteworthy that patients who underwent conversion surgery exhibited a longer survival rate after additionally excluding early disease progression in the chemotherapy only group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, we have implemented a propensity score modeling, producing a matched cohort based on baseline characteristics, as well as the extent of initial biological disease, before palliative chemotherapy and response to chemotherapy. Our findings were consistent with previous studies that advocated conversion surgery if R0 resection could be achieved, even after adjusting for potential confounding factors [9,10,12,21,22]. It is noteworthy that patients who underwent conversion surgery exhibited a longer survival rate after additionally excluding early disease progression in the chemotherapy only group.…”
Section: Discussionsupporting
confidence: 91%
“…It is noteworthy that patients who underwent conversion surgery exhibited a longer survival rate after additionally excluding early disease progression in the chemotherapy only group. In addition, a shorter duration of preoperative chemotherapy was an independent predictor of DFS from conversion surgery, which was contradictory to the previous study [21]. This might in part be attributable to better chemotherapy efficacy in the subgroup of patients with a shorter duration of preoperative chemotherapy, leading to tumor shrinkage that facilitated conversion surgery [23].…”
Section: Discussioncontrasting
confidence: 60%
“…The HRs and 95% CIs for OS could be determined directly 7 , 16 18 or indirectly 19 27 from 13 studies. Nearly, all the studies supported palliative gastrectomy combined with chemotherapy, but only two obtained separated results 16 , 18 when we combined all the HRs for OS in the selected trials, and the results showed that the treatment effect was statistically significant (HR=0.43, 95% CI=0.29–0.65, P <0.001, Figure 2 ), where palliative gastrectomy plus chemotherapy reduced the risk of death by 57% compared with chemotherapy alone.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies of M1 stage gastric cancer reported the actual sites of metastasis. Three trials 19 , 20 , 22 described patients with peritoneal dissemination and two trials 21 , 24 described patients with liver metastasis. For OS, the pooled HR for peritoneal dissemination was 0.46 (95% CI=0.28–0.73, P =0.001, I 2 =61%, Figure 8 ) and the pooled HR for liver metastasis was 0.46 (95% CI=0.33–0.65, P <0.001, I 2 =0%, Figure 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several retro-emotherapy can bring any survival benefit for advanced gastric cancers with a single noncurable factor [17]. In another study of GC with peritoneal metastasis, results showed that patients who gained disease control after chemotherapy had a longer median OS in the gastrectomy group than patients in the non-gastrectomy group [18]. All of these results suggest that response to first-line chemotherapy needs to be a factor for consideration when discriminating the subgroup of patients most likely to benefit from radical or palliative surgery.…”
Section: Discussionmentioning
confidence: 99%